Using Education Technology to Support Students with Special Educational Needs and Disabilities in Low- and Middle-Income Countries - Coflan, Caitlin Moss; Kaye, Thomas (EdTech Hub, 2020)
This brief focuses on how policymakers can make decisions about EdTech to support learners with special educational needs and/or disabilities (SEND) while offering policymakers the rationale and tools to move towards an inclusive approach. It also includes a detailed annex with descriptions, costs, availability, and examples of accessible and assistive technologies.
Keywords: F: Helpdesk response; L:Special education needs and disabilities (SEND); LP: English; _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; ___working_potential_duplicate; _cover:v1; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; dode_eth-src-dode

EdTech for Climate Resilience: A Rapid Evidence Review - Brugha, Meaghan; Azfal, Nimra; Emerusenge, Aime Parfait; Zazai, Rozina; Nagol, Elias (EdTech Hub, 2025)
This Rapid Evidence Review provides a synthesis of evidence related to the use of educational technology for building climate resilience within education systems in low- and middle-income countries. The primary objective of the review is to provide educational stakeholders with an overview of how technology could be effectively leveraged in these contexts, highlighting key design considerations for and potential barriers to effective implementation. The review looked at evidence generated between 2014 and 2025 on how EdTech has or could be used to build climate resilient education systems. An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Sierra Leone Digital Learning Landscape Analysis: Developing the National Digital Learning Strategy - Waziri, Nafisa; Mufti, Abdal; Ramesh Vasudevan, Sharanya; Beoku-Betts, Iman; Oyedele, Oluwatomisin (EdTech Hub, 2025)
In 2024, the World Bank submitted a request to EdTech Hub's Helpdesk to support the Government of Sierra Leone in developing a National Digital Learning Strategy. The Hub initiated the process with the creation of this digital learning landscape analysis. The report identifies achievements and progress to date, as well as key challenges and priority areas going forward. It is based on primary and secondary data collection methods, including key informant interviews, focus group discussions, and a comprehensive desk review. Other relevant sources to gain insight into existing EdTech initiatives, interventions, and challenges within the country were also reviewed. Keywords: EdTech; National Digital Learning Strategy; landscape analysis; Ministry of Basic and Senior Secondary Education; Teaching Service Commission. An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Developing a national EdTech strategy - Coflan, Caitlin; Wyss, Natalie; Thinley, Sangay; Roland, Mark (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen; ⛔ No INSPIRE recid found

TCPD in Tanzania: Phase 2 Round 1 Recommendations - Swai, Calvin; Chachage, Kristeen; Koomar, Saalim; Hennessy, Sara; Massam, Winston; Komba, Aneth; Mwakabungu, Fika; Paskali, Jonathan Hegwa; Anthony, Gervace; Mrope, Winifrida Jacob; Malibichi, Mustapha; Mutura, Emmanuel; et al. (EdTech Hub, 2024)
The study reported here is for Phase 2 of the research project known as ‘The Impact of a Tech-Supported, School-Based Teacher Continuous Professional Development Model on Learning Outcomes in Tanzania’ and part of the global Empowering Teachers Initiative (ETI), which comprises 10 country projects. It is closely aligned with the implementation of ‘MEWAKA’ (Mafunzo Endelevu kwa Walimu Kazini) or Teacher continuous professional development (TCPD), and the Tanzania National TCPD implementation plan. MEWAKA is an innovative, school-based, technology-supported programme currently being implemented by the Government of Tanzania in schools nationwide. The research was co-developed and designed collaboratively between EdTech Hub, the Tanzania Institute of Education (TIE), and Aga Khan University, with consultation from key stakeholders at the ministry level. The work’s current (second) phase focuses on issues of equity, agency, and adaptation in scaling MEWAKA. This policy brief summarises the key findings and recommendations from the first round of data collection for Phase 2 of the research project, conducted in March 2024. Keywords: teachers; teacher professional development; Tanzania; MEWAKA; participatory research An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

EdTech for Out-of-School Children and Youth: A Rapid Evidence Review for the Southeast Asian Region - Barnes, Katrina; Mazari, Haani; Mitchell, Joel; Hayat, Amal; Zhao, Annette; Ullah, Noor; Emerusenge, Aime Parfait; D'Rozario, Jonny; Hinks, Jessica; Thinley, Sangay (EdTech Hub, 2024)
This publication is one part of a series of Rapid Evidence Reviews (RERs) that has been produced by EdTech Hub as part of the ASEAN-UK Supporting the Advancement of Girls’ Education (SAGE) Programme. The programme aims to enhance foundational learning opportunities for all by breaking down barriers that hinder the educational achievements of girls and marginalised learners. The purpose of the RERs is to provide education decision-makers with accessible, evidence-based summaries of good practice in specific areas of EdTech in the Southeast Asian region. They are focused on topics which are particularly relevant to marginalised learners, and how to improve their access to education with technology. All the RERs are available at https://edtechhub.org/. This Rapid Evidence Review (RER) provides an overview of existing literature on the use of educational technology (EdTech) by and for out-of-school children and youth (OOSCY) in Southeast Asia. The review summarises how EdTech is currently being used with OOSCY learners in these contexts, explores how effective these implementations are, and highlights the benefits and challenges of using EdTech with different out-of-school learners. The review’s scope includes the following countries: Brunei, Cambodia, Indonesia, Laos, Malaysia, Myanmar, the Philippines, Singapore, Thailand, Timor-Leste, and Vietnam. The review’s scope includes the following countries: Brunei, Cambodia, Indonesia, Laos, Malaysia, Myanmar, the Philippines, Singapore, Thailand, Timor-Leste, and Vietnam. The RER aims neither to advocate nor discourage the use of technology to support education for OOSCY, but rather to provide an accessible summary of existing evidence on the topic so that educators, policymakers and donors might make informed decisions about the potential role of technology in delivering education for OOSCY. Key words: out-of-school children; rapid evidence review; RER; Southeast Asia; ASEAN; education technology; marginalised learners An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

How Do In-Service Communities of Practice Support Teacher Learning and What Role Can EdTech Play? - Adam, Taskeen; Friese, Laila; Plaut, Daniel (EdTech Hub, 2025)
This Learning Brief is part of the EdTech Hub Learning Brief Series, providing practical resources for people working to improve the use of technology in education. In this brief, we look at how in-service Communities of Practice (CoPs) support teacher learning and how EdTech can enhance this aspect of teacher professional development (TPD) in low- and middle-income countries. In-service CoPs have become an important component of TPD, creating spaces where teachers can share their knowledge and experiences, practice and reflect on pedagogical approaches, and support one another through classroom challenges. We focus on EdTech Hub’s work in design-based implementation research for TPD with particular reference to large-scale national TPD programmes in Tanzania, Malawi, and Sierra Leone. CoPs have been an essential part of these programmes. Cross-cutting insights and similarities identified across these programmes surface effective practices in designing and implementing CoPs, including the role of EdTech in enabling, supporting, or enhancing them. We present findings and recommendations that inform how various tech modalities used in CoPs have been instrumental in supporting TPD at the ‘teacher’, ‘school’, and ‘system’ levels. Lastly, we explore areas that require further research, namely, the need to measure the impact of CoPs, specifically regarding improved classroom instruction and learning outcomes. There is minimal information on the cost-effectiveness of CoPs and the use of technologies within them; this area merits further research. More testing could also be done to better understand facilitators’ training and support needs and their level of ease with implementing their roles in CoPs. Keywords: Teacher professional development; teacher continuous professional development; learning management systems; communities of practice; teacher learning circles An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Note de conseils sur la plateforme numérique - Messa, Angele; Koomar, Saalim; Mitchell, Joel (EdTech Hub, 2025)
This document is a guidance note on digital platforms, specifically focusing on e-learning and the use of Opale and Moodle software. It aims to support the implementation of a digital learning platform in Madagascar. The report addresses questions and challenges faced by the Ministry of National Education in developing and deploying digital educational content. It covers various aspects of e-learning, including evaluation methods, content structuring, accessibility, interactivity, and technical requirements. Key topics include different evaluation models, types of e-learning evaluation (formative and summative), guidelines for using Opale, tablet specifications for online learning, ensuring course accessibility, and using Moodle both online and offline. The document also provides a checklist for ensuring quality in e-learning course development and implementation. Keywords: e-learning; Moodle; Opale; digital platform; accessibility; usability; Madagascar Ce document est une note d’orientation sur les plateformes numériques, avec un accent particulier sur l’e-learning et l’utilisation des logiciels Opale et Moodle. Il vise à soutenir la mise en place d’une plateforme d’apprentissage numérique à Madagascar. Le rapport aborde les questions et défis rencontrés par le Ministère de l’Éducation Nationale dans le développement et le déploiement de contenus éducatifs numériques. Il traite de divers aspects de l’e-learning, notamment les méthodes d’évaluation, la structuration des contenus, l’accessibilité, l’interactivité et les exigences techniques. Les principaux sujets incluent les différents modèles d’évaluation, les types d’évaluation en e-learning (formative et sommative), les recommandations pour l’utilisation d’Opale, les spécifications des tablettes pour l’apprentissage en ligne, l’accessibilité des cours et l’utilisation de Moodle en mode en ligne et hors ligne. Le document propose également une liste de contrôle pour garantir la qualité du développement et de la mise en œuvre des cours en e-learning. Mots clés: e-learning; Moodle; Opale; platforme numériques; accessibilité; usabilité; Madagascar An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence; _r:AddedByZotZen